Imaging findings of an isolated gastric tuberculosis case mimicking lymphoma and infiltrative gastric cancer - Bahadır Öztürk,; Mehmet Selim Nural,; Özgür Ecemiş,; Murat Danacı, (Turkish Journal of Gastroenterology, 2019)
-